Support Vector Machine for Classification Based on Fuzzy Training Data - Ai-Bing Ji; Jia-Hong Pang; Shu-Huan Li; Jian-Ping Sun (Proceedings (International Conference on Machine Learning and Cybernetics.), 2006)
Support vector machines (SVMs) have been very successful in pattern recognition and function estimation problems, but in the support vector machines for classification, the training examples are non-fuzzy input and output is y=plusmn1;. In this paper, we introduce the support vector machine in which the training examples are fuzzy input, and give some solving procedure of the support vector machine with fuzzy training data